On Fixed Point Results in Partial b-Metric Spaces - Haitham Qawaqneh; Mohd Salmi Md Noorani; Hassen Aydi; Amjed Zraiqat; Arslan Hojat Ansari (Journal of Function Spaces, 2021)
Partial b-metric spaces are characterised by a modified triangular inequality and that the self-distance of any point of space may not be zero and the symmetry is preserved. The spaces with a symmetric property have interesting topological properties. This manuscript paper deals with the existence and uniqueness of fixed point points for contraction mappings using triangular weak α-admissibility with regard to η and C-class functions in the class of partial b-metric spaces. We also introduce an example to demonstrate the obtained results.